Global systematic review of biomechanical and ergonomic assessment outcomes among urban transit operators - Bayu Yoni Setyo Nugroho; Ratih Pramitasi; Supriyono Asfawi; Muhammad Ashraf Fauzi (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Urban transit operators, including bus drivers, train operators, and metro personnel, are chronically exposed to biomechanical stressors and ergonomic hazards predisposing them to musculoskeletal disorders (MSDs), whole-body vibration (WBV)-related spinal pathology, and psychosocial morbidity. To systematically identify, critically appraise, and synthesise biomechanical and ergonomic assessment outcomes among urban transit operators worldwide. Research Methodology: This systematic review followed the PRISMA 2020 guidelines and used the PICOS framework. English-language studies published between 2000 and 2024 were retrieved from PubMed, Medline, Embase, Scopus, Global Health, and Google Scholar. Quality appraisal employed the JBI Critical Appraisal Checklist for Analytical Cross-Sectional Studies. Narrative synthesis was applied due to methodological heterogeneity, which precluded meta-analysis. Results: Of 312 identified records, 45 Cross-Sectional studies from 23 countries (n = 12,859 workers) met the inclusion criteria. Bus drivers comprised 52% of the study population. The predominant outcome domain was MSDs (31%), followed by WBV exposure (24%), psychosocial and fatigue outcomes (18%), postural risk (11%), ergonomic risk assessment (9%), and occupational injuries (9%). Low back pain (LBP) prevalence ranged from 43% to 78%. WBV exposures frequently exceeded the 0.5 m/s² Exposure Action Value under EU Directive 2002/44/EC. Quality appraisal rated 60% of studies as low risk, 31% as moderate risk, and 9% as high risk of bias. Conclusion: Urban transit operators represent a high-risk occupational group for biomechanical and ergonomic hazards. Standardised longitudinal studies, objective exposure assessment, and equitable geographic representation are urgently needed to inform globally applicable prevention guidelines.